EVALUASI DESAIN INSTALASI PENGOLAHAN AIR PDAM IBU KOTA KECAMATAN PRAMBANAN KABUPATEN KLATEN - Arifiani, Nur Fajri; Hadiwidodo, Mochtar (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
To  supply  good  water  quality,  quantity,  and  continuity  is  needed  an  Water  Treatment Plant (WTP).  The  unit  process  and  operation  is  dependent  on  quality  of    water  resources.  WTP in Klaten Unit Prambanan had a design flow of 20 L/s and had quality of water resources which is more than  water  parameter  regulation.  There  are  ferrous  (3,36  mg/L),  mangan  (0,58  mg/L), colour (159  TCU),  and  bad  odour.  So,  it  is  needed  aeration,  koagulation,  flocculation, sedimentation, and filtration units to separate them. Quality of water  efluent in this WTP is less than water parameter regulation. There are ferrous (0,18 mg/L) , mangan (0,21 mg/L), colour (3 TCU), and no odour. But, its need more improvement to optimalize reducing parameters.